Underwater Macroplastic Detection Using Imaging Sonars - Flores, Natasha Y.; Oswald, Stephanie B.; Leuven, Rob S. E. W.; Collas, Frank P. L. (Frontiers in Environmental Science, 2022)
Plastic pollution in the ocean occurs mainly via riverine transport. In rivers, plastic is pervasive in sediments and in the water column. Monitoring of floating plastics in rivers is time consuming as it is usually collected using nets and classified by hand, or counted and classified visually. To make plastic detection in the water column more time- and cost-efficient, there is a need to explore remote sensing options. Here we present the results of two semi-controlled pilot tests in standing water using two imaging sonar technologies: an Adaptive Resolution Imaging Sonar (ARIS) sonar and a low-cost side-scan sonar (SSS). Additionally, the ARIS sonar was tested in flowing water at a sheltered shore channel behind a longitudinal training dam in the river Waal, the Netherlands. Both technologies were able to detect 100% of the macroplastics tested in standing water. The ARIS sonar provided higher resolution images of the targets tested due to its high operation frequency detecting macroplastics down to a size of 1 cm2. The ARIS sonar detected macroplastics in the field, however, the detection decreased to 67% in flowing water. This sonar was limited to the 2D horizontal position of targets. The SSS is a low-cost option for monitoring of plastics and is integrated with CHIRP sonar technology that combines side and down imaging providing the 3D position of targets. For future monitoring, an ARIS sonar in motion or two ARIS sonars used simultaneously may provide the necessary 3D spatial information of plastic targets.